Deep brain stimulation of the ventral striatum increases BDNF in the fear extinction circuit - Do-Monte, Fabricio H.; Rodriguez-Romaguera, Jose; Rosas-Vidal, Luis E.; Quirk, Gregory J. (Frontiers in Behavioral Neuroscience, 2013)
Deep brain stimulation (DBS) of the ventral capsule/ventral striatum (VC/VS) reduces the symptoms of treatment-resistant obsessive compulsive disorder (OCD), and improves response to extinction-based therapies. We recently reported that DBS-like stimulation of a rat homologue of VC/VS, the dorsal-VS, reduced conditioned fear and enhanced extinction memory (Rodriguez-Romaguera et al, 2012). In contrast, DBS of the ventral-VS had the opposite effects. To examine possible mechanisms, we assessed the effects of VS DBS on the expression of the neural activity marker Fos and brain-derived neurotrophic factor (BDNF), a key mediator of extinction plasticity in prefrontal-amygdala circuits. Consistent with decreased fear expression, DBS of dorsal-VS increased Fos expression in prelimbic and infralimbic prefrontal cortices and in the lateral division of the central nucleus of amygdala, an area that inhibits amygdala output. Consistent with improved extinction memory, we found that DBS of dorsal-VS, but not ventral-VS, increased neuronal BDNF expression in prelimbic and infralimbic prefrontal cortices. These rodent findings are consistent with the idea that clinical DBS of VC/VS may augment fear extinction through an increase in BDNF expression.